The Impact of Digital Transformation on the Quality of Financial Reports A Field Study in a Sample of Banks Listed in the Iraqi Stock Exchange - Mustafa Saeed Hasan (Scholars Digest Publishing, 2023)
The study aims to recognize the concept and objectives of digital transformation and the quality of financial reports and measurement models with qualitative characteristics of accounting information, to achieve the study's objective, the study dealt with a questionnaire form designed to survey accountants, department heads, account managers and banking executives. This form was distributed to banks listed on the Iraqi Stock Exchange, and its number was swallowed. (102) A valid form for statistical analysis, the researcher has used statistical methods to analyze the results and test hypotheses: Alpha Cronbach Persistent Coefficient, Pearson Binding Coefficient, Metrics for Descriptive Statistics and Simple Linear Regression Analysis and the study reached a set of conclusions, the most important of which was the inverse correlation between digital transformation and the quality of the financial report. whenever the economic unit moves towards digital transformation whenever this results in the adequacy and reliability of accounting information and thus the benefit to its users, The study also found a moral impact of digital transformation on the quality of financial reports (appropriate and genuine representation).
Keywords: Digital Transformation, Quality of Financial Reports, Relevance, Honest Representation.